Local regulation of immune genes in rainbow trout (Oncorhynchus mykiss) naturally infected with Flavobacterium psychrophilum - Muñoz-Atienza E. (2019)
The authors want to thank Lucía González and Laura Fernández for technical assistance. Dr. Erin Bromage (University of Massachusetts Dartmouth, USA) is also acknowledged for supplying the anti-IgD and anti-CD3 antibodies used in this study. This work was supported by the European Research Council (ERC Consolidator Grant 2016 725061 TEMUBLYM). Carlos Távara would like to acknowledge the financial support from the Master Program in Aquatic Animal Health of the UPCH subsidized by Cienciactiva of CONCYTEC (Management Agreement No. 230-2015- FONDECYT-DE-PROMOCION 2). Carlos Távara also would like to acknowledge Vitapro S.A. for the interest in this research and support in the development of this work. E. Muñoz-Atienza holds a Juan de la Cierva-Formación Postdoctoral Contract (FJCI-2015-24452) funded by the Spanish Ministry of Economy, Industry and Competitiveness.